Metacognition and Digital Reading: How Medium Platform Enhances Self-Awareness and Comprehension in Learners - Fenny Thresia; Kayla Zalfa; Aulia Hanifah Qomar (English Education Study Program, 2026)
This study explores how the Medium platform contributes to the development of metacognitive awareness and reading comprehension in digital learning environments. In the era of technology-based education, learners are increasingly required to become active and independent readers who can regulate their own learning processes. Metacognition plays a significant role in helping learners monitor, evaluate, and improve their understanding while reading. At the same time, reading comprehension remains a major challenge in many educational contexts, including Indonesia. Through its long-form articles, interactive features, and diverse academic content, Medium provides learners with opportunities to engage in reflective and critical reading practices. The platform encourages users to analyze information, identify comprehension gaps, and develop critical thinking skills through continuous interaction with meaningful texts. Furthermore, Medium supports both literacy development and higher-order thinking by creating a digital space that promotes deep cognitive engagement rather than passive content consumption. Therefore, this article argues that the Medium platform serves as an effective digital tool for enhancing learners’ metacognitive awareness, reading comprehension, and critical thinking abilities in contemporary education.